Pengaruh Good Governance, Kompetensi SDM dan Sistem Pengendalian Intern pada Kualitas Laporan Keuangan - Gita Saraswati, I Gusti Ayu; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 27 No 3 (2019)DO - 10.24843/EJA.2019.v27.i03.p23, 2019)
The purpose of this study was to determine the effect of good governance, HR competencies and internal control systems on the quality of financial reports in the Denpasar City government. The population of the study was 36 Regional Organizations (OPD) of Denpasar City. nonprobability sampling, which is saturated sampling, is a method of selecting samples used, the sample obtained is 108 respondents. Questionnaire is a data collection method used in this study. Respondents to this research questionnaire were to the head of department, head of the sub-section of finance and treasurer. The analysis technique used is multiple linear regression analysis techniques. Based on the results of data analysis it was found that good governance, HR competence and internal control systems had a positive influence on the quality of financial statements. Keywords : Financial report quality; good governance; human resource competence; internal control system